Perspective Plan 2001 Volume-I Government of Karnataka - Planning Commission (Planning Commission, 1989)
The practices in the past have reduced people to mere applicants, aggravated dependencies rather than strengthened self-reliance, generated cowardice rather than courage. Among those who were chosen to serve the people, these practices bred and fostered arrogance, complacency and corruption - inherent in a scheme of patronage distribution.
Government of Karnataka